History of Geology:: Placer Gold Mining in Pleistocene Glacial Sediments of the Cariboo District, British Columbia, Canada 1858-1988 - Eyles, N.; Kocsis, S. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1988)
Summary The Cariboo placer mining district of central British Columbia, based on the communities of Wells/Barkerville, is a classic gold rush area of the late 1850s where gold mining still continues. Production started in 1858 and by 1861 Barkerville was the largest town northof San Francisco and west of Chicago. Today the area accounts for almost 30% of the province's annual total placer gold output, valued at about $9M. Gold apparently concentrated in near surface positions by deep tertiary weathering and supergene enrichment of Mississippian-Permian metasediments, has been incorporated into unconsolidated sediments by Pleistocene glacial erosion. Much anecdotal information is available regarding past mining operations but geological data are few. On-going glacial sedimentological work in the area is trying to model the distribution of placers and to develop exploration strategies. This work is revealing much new data regarding the geology of historic and current placer mines.